4-Aminophenylboronic acid dimer sensitized carbon nanotubes for the construction of portable and disposable sulfide electrochemical sensors - Thiruppathi, Murugan; Velusamy, Nithya; Tsai, Ching-Ying; Chang, Yue-Ning; Chen, Cheng-Che; Fa, Yu-Chen; Annie Ho, Ja-an (Electrochimica acta, 2024)
•Aminophenylboronic acids are electro-dimerized on f-CNT, and used for sulfide sensor.•Our portable electrochemical sensor for measuring sulfide is without surface fouling.•A 3-fold lower level of sulfide is found in diabetic patients than in healthy people.•Our method helps to discriminate cancer cells from normal ones based on sulfide concentration. Abnormal sulfide levels in serum can cause kidney failure, Alzheimer's, Parkinson's, stroke, diabetes, and even cancer. Therefore, maintaining proper sulfide balance is crucial for managing and preventing these conditions. Electrochemical approaches have emerged as potential alternatives for sulfide detection. However, the adsorption of elemental sulfur on the working electrode leads to surface fouling and passivation, posing a significant challenge in developing reliable electrochemical methods for sulfide detection. In this study, we present a portable and surface fouling-free electrochemical system that utilizes functionalized multi-walled carbon nanotubes and 4-aminophenylboronic acid dimers for accurate sulfide measurement. The sensor showed excellent electrocatalytic activity to sulfide and antifouling activity to possible interferences. The method had a linear range from 10 µM to 2 mM and a detection limit of 2.3 µM. The effectiveness and applicability of this method were evaluated by analyzing sulfide levels in different serum samples and comparing the results with their glucose levels. As both blood glucose and sulfide levels can serve as indicators of certain health conditions, such as diabetes or sulfur metabolism disorders, this comparison provides valuable insights. Importantly, no complicated sample pretreatment was involved, thus this method can be easily adopted as a point-of-care diagnostic device. Additionally, the study also revealed a higher concentration of sulfide in cancer cells than in normal cells, offering a new development direction for differentiating between cancer cells and normal cells. [Display omitted]